Immediate breastfeeding and skin-to-skin contact as a physiological approach to third-stage labour management: an observational study - Gupta, Ruchika; Kishore, Swathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The third stage of labour is critical for preventing postpartum haemorrhage and ensuring maternal and neonatal safety. Early initiation of breastfeeding combined with immediate skin-to-skin contact (SSC) may enhance physiological uterine contraction and improve neonatal outcomes. This study aimed to assess the effectiveness of breastfeeding initiation and SSC immediately following delivery during the third stage of labour in a tertiary care hospital in India. Methods: This observational study was conducted in the Department of Obstetrics and Gynaecology at Shimoga Institute of Medical Sciences, Shivamogga, Karnataka, India, over a six-month period from January 2023 to June 2023. The study included term pregnant women who delivered singleton infants. Immediately after birth, newborns were placed in skin-to-skin contact on the mother’s bare chest, and breastfeeding was initiated during the third stage of labour. Maternal outcomes assessed included the duration of the third stage of labour, changes in haemoglobin levels, and the requirement for additional uterotonics. Neonatal outcomes focused on breastfeeding success and morbidity. Results: The median duration of the third stage was significantly shortened, with 90% of placental separation occurring within 10 minutes. Participants exhibited minimal haemoglobin drop and a reduced need for additional uterotonics (12%). Breastfeeding initiation within the first hour was achieved in 98% of neonates, with no adverse neonatal outcomes reported. Conclusions: Initiating breastfeeding with immediate SSC during the third stage of labour appears to be a safe and effective physiological intervention that enhances uterine contraction, reduces maternal blood loss, and promotes successful neonatal adaptation. This low-cost approach holds promise for improving maternal and neonatal health outcomes, particularly in resource-limited settings.